Effects of Cu doping on the electronic structure and magnetic properties of MnCo2O4 nanostructures. (13th September 2017) - Pramanik, Prativa; Thota, Subhash; Singh, Sobhit; Joshi, Deep Chandra; Weise, Bruno; Waske, Anja; Seehra, M S
Abstract: Reported here are the results and their analysis from our detailed investigations of the effects of Cu doping ( x ⩽ 0.2 ) on the electronic structure and magnetic properties of the spinel M n C o 2 O4 . A detailed comparison is given for the x = 0 and x = 0.2 cases for both the bulk-like samples and nanoparticles. The electronic structure determined from x-ray photoelectron spectroscopy and Rietveld analysis of x-ray diffraction patterns shows the structure to be: ( C o 3 + )A [ M n 3 + C o ( 1 − x ) 2 + C u x 2 + ]B O 4 i.e. C u 2 + substitutes for C o 2 + on the octahedral B-sites. For the bulk samples, the ferrimagnetic T C = 184 K for x = 0 is lowered to T C = 167 K for the x = 0.2 sample, this decrease being due to the effect of Cu doping. For the nanosize x = 0 ( x = 0.2 ) sample, the lower T C = 165 K ( T C = 155 K) is observed using ∂ ( χ d c T ) / ∂ T analysis, this lowering being due to finite size effects. For T > T C, fits of dc paramagnetic susceptibility data of χ − 1 versus T in nanosize samples to the Néel expression are used to determine the exchange interactions between the A and B sites with exchange constants: J A A / k B ∼ 8.4 K (4.1 K), J B B / k B ∼ 21.2 K (16.3 K) and J A B / k B ∼ 13.9 K (13.8 K) for x = 0 ( 0.2 ) . The temperature dependence of ac susceptibilities χ ′ ( T ) and χ ″ ( T ) at different frequencies shows that in bulk samples of x = 0 and x = 0.2, the transition at T C is the normal second order transition. But for the nanosize x = 0 and 0.2 samples, analysis of the ac susceptibilities shows that the ferrimagnetic transition at T C is followed by a re-entrant spin-glass transition at lower temperatures T S G ∼ 162 K (138 K) for x = 0 ( x = 0.20 ). Analysis of the ac susceptibilities, χ ′ ( T ) and χ ″ ( T ), versus T data is done in terms of two scaling laws: (i) Vogel–Fulcher law [ τ = τ o exp ⁡ ( E a / ( k B ( T − T o ) ) ) ] ; and (ii) power law of critical slowing-down τ / τ o = [ ( T P / T S G ) − 1 ] − z ν . These fits confirm the existence of glassy behavior below T SG with the parameters z ν = 6.01 (8.91), τ o ∼ 6.18 × 10 − 15 (9.6 × 10 − 14 ) and T S G ∼ 162 K (̃138 K) for the samples x = 0 (0.2), with similar results obtained for other samples. The linear behavior of the peak maximum in χ a c ( T ) versus H d c 2 / 3 (AT-line) further supports the existence of glassy states in nanosize samples. For T < T C, the temperature and composition dependence of the hysteresis loop parameters are investigated; all the samples with x ⩾ 0.1 have the coercivity H C and remanence M R ∼ 0 . Since the results reported here in these nanostructures are significantly different from those in bulk M n C o 2 O 4, further investigations of their magnetic structures using neutron diffraction are warranted.